Integrated care for childhood epilepsy: ongoing challenges and lessons for other long-term conditions. Issue 11 (24th May 2016) - Bali, Amit; Hargreaves, Dougal S; Cowman, John; Lakhanpaul, Monica; Dunkley, Colin; Power, Millie; Cross, J Helen
Abstract : Epilepsy care has been identified as a major global issue—and there are many recognised concerns in the UK for children and young people with the condition. A proposed new model could help to increase multisector integration, facilitate better outcomes and offer lessons for improving care of other long-term conditions.